Badania jakości węgla według wymagań unii europejskiej na przykładzie złoża węgla brunatnego "Bełchatów" = The coal quality testing as required by the european union for example the "Bełchatów" lignite deposit - Hycnar, Elżbieta; Ratajczak, Tadeusz; Jończyk, Waldemar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The energy coal processing is associated with the emissions into the atmosphere of many compounds having a negative impact on the environment. In order to reduce the emissions, it is necessary to conducting systematic research of coal quality. The research, in addition to the standard determination of coal physico-chemical parameters should be cover also study the contents of Cd, Pb and Hg, the elements particular nuisance to the environment.
Keywords: węgiel brunatny; złoże "Bełchatów"; badania jakości węgla; pierwiastki toksyczne w węglu; lignite; "Bełchatów" deposit; coal quality testing